Program MBKM: Magang Industri di UMKM Marasoe - Yayan Firmansyah; Indah Eva Saffanah; Isna Amelia Nurhamidah; Esra Mariana Sitorus; Desy Aryani (Sekolah Tinggi Ekonomi Bisnis Syariah Bina Mandiri, 2022)
This industrial internship aims to provide students with experience so that they can implement what they have learned in the Business Administration Study Program to real activities in the business world. This activity is useful to increase knowledge on how to run a business. Starting from the selection of product materials, selecting the target market, how to do promotions that attract the attention of the target market, and knowing how to serve consumers well or deal with consumers who complain. The implementation method is carried out online at an online business for women’s tops “Marasoe”. The results obtained from this industrial internship are useful knowledge for students. As for the company, getting clothing design references for future production, clothing design references made by students were sold out, thus increasing customer interest in Marasoe, getting help with content ideas, getting help in replyinig to incoming messages, and getting a significant increase in Instagram followers.